Editorial commentary on special issue of COVID-19 pandemic - Yang, Wei (J Biomed Res, 2020)
This special issue of The Journal of Biomedical Research presents rigorous empirical analysis related to COVID-19 research in responding to the current global COVID-19 pandemic. Selected articles from different disciplines not only offer broader perspectives on combating the outbreaks, but also disseminate the most updated findings on this new challenge for human being to the field.